Low modulus hot melt pressure sensitive adhesive for optical film lamination
Patent Information
- Application Number
- CN202611398556.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-09-10
AI Technical Summary
Existing hot melt pressure-sensitive adhesives have problems in optical thin film lamination applications, such as insufficient component compatibility, difficulty in balancing low modulus and high cohesive strength, and phase separation leading to increased haze.
A low-modulus hot-melt pressure-sensitive adhesive was prepared by using hydrogenated styrene-isoprene-styrene block copolymer, polyisobutylene, hydrogenated alicyclic hydrocarbon resin, and single-ended polyether reaction-modified flexible compatibility components through a mixing process. Combined with a hindered phenolic and phosphite antioxidant system, the compatibility and antioxidant properties were improved.
It achieves high optical transparency, high holding power, and low thermal and oxidative degradation and yellowing tendency of low modulus hot melt pressure-sensitive adhesive, solves the problem of balancing component compatibility and modulus strength, and reduces the risk of increased haze.
Smart Images

Figure CN122878900B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hot melt pressure-sensitive adhesive technology, and specifically to a low-modulus hot melt pressure-sensitive adhesive for optical thin film lamination. Background Technology
[0002] Optical thin-film lamination technology is widely used in electronic display devices such as liquid crystal displays (LCDs), organic light-emitting diode (OLED) displays, touch panels, and automotive display modules. During the assembly of display modules, various optical thin films, such as polarizers, brightness enhancement films, diffusion films, and protective films, need to be laminated together using adhesives to form a multilayer film structure with specific optical functions. In optical thin-film lamination, adhesives not only provide mechanical bonding but also need to meet comprehensive performance requirements such as optical transparency, weather resistance, and stress buffering.
[0003] Currently, solvent-based acrylic pressure-sensitive adhesives and silicone pressure-sensitive adhesives are mainly used in the field of optical thin film lamination. Solvent-based acrylic pressure-sensitive adhesives require a large amount of organic solvents during coating, resulting in volatile organic compound emissions. Furthermore, they require high-temperature drying after coating, leading to high energy consumption and limited production efficiency. While silicone pressure-sensitive adhesives possess excellent high-temperature resistance and low modulus characteristics, they are more expensive and have insufficient wettability on low surface energy substrates, necessitating surface treatment of the substrate before coating.
[0004] Hot melt pressure-sensitive adhesives (PSAs) have been widely used in general fields such as labels and tapes due to their advantages of being solvent-free, having fast coating speeds, and low energy consumption. However, applying PSAs to optical film lamination faces the following technical challenges: First, conventional PSAs use styrene-isoprene-styrene block copolymers or styrene-butadiene-styrene block copolymers as the matrix. Their unsaturated backbones are prone to degradation and yellowing under ultraviolet light and heat-oxidation, leading to deterioration of optical properties. Second, although hydrogenated styrene block copolymers have excellent aging resistance, their compatibility with tackifying resins and plasticizers is limited, making them prone to phase separation and resulting in increased haze in the adhesive layer. Third, to meet the requirements of low stress and high wettability in optical film lamination, PSAs need to have a low storage modulus. However, reducing the modulus often comes at the cost of sacrificing cohesive strength, leading to decreased holding power and high-temperature creep.
[0005] Therefore, developing a hot melt pressure-sensitive adhesive that combines low modulus, high optical transparency, high holding power, and low yellowing tendency is of great significance for promoting the solvent-free development of optical thin film lamination technology. Summary of the Invention
[0006] The purpose of this invention is to address the problems existing in the application of hot-melt pressure-sensitive adhesives in optical thin film lamination, such as insufficient component compatibility, difficulty in balancing low modulus and high cohesive strength, and increased haze due to phase separation. This invention provides a low-modulus hot-melt pressure-sensitive adhesive for optical thin film lamination, which exhibits low storage modulus, high optical transparency, high holding power, and low tendency for thermo-oxidative degradation and yellowing. This invention also provides a method for preparing the aforementioned low-modulus hot-melt pressure-sensitive adhesive and an optical thin film lamination intermediate using this hot-melt pressure-sensitive adhesive.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is: a low-modulus hot-melt pressure-sensitive adhesive for optical thin film lamination, comprising, by weight, the following raw materials: 38-48 parts of hydrogenated styrene-isoprene-styrene block copolymer, 12-20 parts of polyisobutylene, 30-40 parts of hydrogenated alicyclic hydrocarbon resin, 6-13 parts of cycloalkyl white oil, 6-11 parts of single-end polyether reaction-modified flexible compatibility component, 0.3-0.5 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and 0.15-0.35 parts of tris(2,4-di-tert-butylphenyl) phosphite.
[0008] Furthermore, the single-ended polyether reactive modified flexible compatibility component is made from the following raw materials in parts by weight: 100 parts of maleic anhydride-grafted hydrogenated styrene-ethylene / butene-styrene block copolymer, 8.6-16.7 parts of single-ended primary amino polyether, and 14-22 parts of hydrogenated alicyclic hydrocarbon resin.
[0009] The amount of hydrogenated alicyclic hydrocarbon resin in the low-modulus hot-melt pressure-sensitive adhesive formulation does not include the hydrogenated alicyclic hydrocarbon resin contained in the single-end polyether reaction-modified flexible compatibility component.
[0010] Furthermore, the molar amount of primary amino groups in the single-terminated primary amino polyether is 1.03-1.05 times the molar amount of maleic anhydride groups in the maleic anhydride graft copolymer; during the reaction, at least some of the maleic anhydride groups undergo ring-opening amidation and / or dehydration imidization with the primary amino groups to form a reaction-modified polymer containing polyoxypropylene ether side chains.
[0011] Furthermore, the single-ended polyether reaction-modified flexible compatibility component is prepared according to the following steps: A1. The maleic anhydride-grafted hydrogenated styrene-ethylene / butene-styrene block copolymer and the single-terminated primary amino polyether are dried at 75-90℃ and a gauge pressure of -0.080 to -0.095 MPa for 2-4 hours to obtain the dried maleic anhydride-grafted hydrogenated styrene-ethylene / butene-styrene block copolymer and the dried single-terminated primary amino polyether.
[0012] A2. The dried maleic anhydride-grafted hydrogenated styrene-ethylene / butene-styrene block copolymer is added to a closed mixing equipment and mixed for 5-10 minutes under nitrogen protection, 155-165℃ and 40-70r / min. The dried single-terminal primary amino polyether is then added, and the temperature is raised to 175-185℃ and mixed for 35-60 minutes to obtain the reaction-modified product.
[0013] A3. Add the hydrogenated alicyclic hydrocarbon resin to the reaction-modified product, mix at 170-180℃ and 40-70 r / min for 10-20 min, then devolatilize at 170-180℃ and gauge pressure of -0.080 to -0.095 MPa for 10-20 min, extrude and pelletize to obtain the single-end polyether reaction-modified flexible compatibility component.
[0014] Furthermore, the melt flow rate of the hydrogenated styrene-isoprene-styrene block copolymer is 3-15 g / 10 min under conditions of 230°C and 2.16 kg load.
[0015] Furthermore, the number-average molecular weight of the polyisobutylene is 30,000-90,000.
[0016] Furthermore, the single-terminal primary amino polyether is a polyoxypropylene ether having a primary amino group at one end and a methoxy group at the other end, with a primary amine value of 0.90-0.98 meq / g, which is equivalent to an amine value of 50.5-55.0 mg KOH / g based on KOH.
[0017] Furthermore, the ring and ball softening point of the hydrogenated alicyclic hydrocarbon resin is 95-125°C, and the Gardner color number is no higher than No. 1.
[0018] Furthermore, the primary amine value of the single-terminated primary amine polyether is 0.94 meq / g; when the maleic anhydride mass fraction of the maleic anhydride graft copolymer is 0.8%, 1.0%, and 1.4%, the amount of single-terminated primary amine polyether relative to 100 parts of maleic anhydride graft copolymer is 9.03 parts, 11.28 parts, and 15.80 parts, respectively, and the molar ratio of primary amine to maleic anhydride groups is 1.04 in all cases.
[0019] This invention also provides a method for preparing a low-modulus hot-melt pressure-sensitive adhesive for optical thin film lamination, comprising the following steps: S1. The hydrogenated styrene-isoprene-styrene block copolymer, polyisobutylene, hydrogenated alicyclic hydrocarbon resin and single-ended polyether reaction-modified flexible compatible component are dried at 65-85℃ and a gauge pressure of -0.080 to -0.095 MPa for 2-4 hours.
[0020] S2. Add the cycloalkyl white oil and hydrogenated styrene-isoprene-styrene block copolymer to a closed mixing equipment and mix for 20-35 minutes under nitrogen protection, 155-170℃ and 40-80r / min.
[0021] S3. Add polyisobutylene and single-ended polyether reaction-modified flexible compatibility components, and mix for 15-30 minutes at 160-175℃ and 40-80r / min.
[0022] S4. Add the hydrogenated alicyclic hydrocarbon resin in 2-4 batches of equal mass. After each batch is added, mix them at 160-175℃ and 40-80r / min for 8-15min.
[0023] S5. Add pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl)phosphite, and mix for 15-25 minutes at 160-175℃ and 40-80 r / min.
[0024] S6. Degas for 10-20 minutes at 160-175℃ and gauge pressure of -0.080 to -0.095 MPa, then filter through a 100-200 mesh metal filter to obtain the low modulus hot melt pressure-sensitive adhesive.
[0025] Furthermore, in steps S2 to S5, the material temperature inside the mixing equipment is maintained at 165-172℃; in step S6, a 150-180 mesh metal filter is used for filtration, and the material temperature is 165-175℃ during filtration.
[0026] An optical thin film bonding intermediate includes a first optical film, a release material, and a hot-melt pressure-sensitive adhesive layer disposed between the first optical film and the release material. The first optical film is a 50 μm thick polyethylene terephthalate (PET) film, and the release material is a 50 μm thick PET release film with its release surface facing the hot-melt pressure-sensitive adhesive layer. The hot-melt pressure-sensitive adhesive layer is formed from the aforementioned low-modulus hot-melt pressure-sensitive adhesive and has a thickness of 10-50 μm. The PET release film serves as a temporary protection and transfer carrier for the hot-melt pressure-sensitive adhesive layer and is peeled off from the surface of the hot-melt pressure-sensitive adhesive layer during use to allow the exposed adhesive surface to bond with another optical substrate to be bonded.
[0027] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention introduces a single-ended polyether reaction-modified flexible compatibility component. By utilizing the compatibility between its hydrogenated styrene block copolymer backbone and the HSIS matrix, as well as the interfacial regulation effect of the polyoxypropylene ether side chain, it is beneficial to improve the mixing uniformity of the hot melt pressure-sensitive adhesive system and reduce the risk of increased haze caused by macroscopic phase separation.
[0028] 2. Single-terminated primary amino polyethers are at least partially fixed to the polymer backbone by reacting with maleic anhydride groups in maleic anhydride graft copolymers. Compared with direct physical blending of polyethers, this helps to reduce the migration and exudation of free polyethers; the flexibility of polyether segments helps to improve the stress buffering capacity of the adhesive layer.
[0029] 3. The present invention determines the amount of single-terminal primary amino polyether based on the primary amine value and maleic anhydride mass fraction of the raw material batch, and controls the molar ratio of primary amino to maleic anhydride groups to be 1.03-1.05, so that the maleic anhydride groups have sufficient reaction conditions, while avoiding excessive single-terminal primary amino polyether to increase free low molecular weight components.
[0030] 4. This invention uses HSIS with a styrene structural unit mass fraction of 13% and an isoprene structural unit hydrogenation degree of 99.2% and polyisobutylene with a number average molecular weight of 55,000 to maintain the cohesive strength provided by the physical cross-linking domains and long chain entanglements of styrene while reducing the rigidity of the adhesive layer.
[0031] 5. This invention uses a styrene block copolymer with a high degree of hydrogenation as the matrix resin and a composite antioxidant system composed of hindered phenolic primary antioxidant and phosphite auxiliary antioxidant, which is beneficial to reduce thermo-oxidative degradation and yellowing tendency during melt processing and use.
[0032] 6. This invention employs a solvent-free hot-melt mixing process, which does not use any organic solvents and produces no volatile organic compounds. Furthermore, the phased addition of hydrogenated alicyclic hydrocarbon resin avoids the problems of sudden drops in viscosity and uneven mixing caused by adding a large amount of resin at once, thus improving the uniformity of dispersion of each component in the matrix. Attached Figure Description
[0033] Figure 1 The ATR-FTIR comparison spectra of MAH-g-SEBS, single-terminated primary amino polyether, unreacted physical mixture, and reaction-modified product R1 in Example 1 of this invention are shown. Detailed Implementation
[0034] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. The described embodiments are used to illustrate the present invention and are not intended to limit the scope of protection of the present invention. Based on the technical content disclosed in the present invention, equivalent substitutions or conventional adjustments that can be made by those skilled in the art should all fall within the scope of protection of the present invention.
[0035] Technical features / manufacturer models of the raw materials used in the examples and comparative examples: Hydrogenated styrene-isoprene-styrene block copolymer (HSIS): styrene structural unit mass fraction is 13%, isoprene structural unit hydrogenation degree is 99.2%, melt flow rate is 8 g / 10 min under 230℃ and 2.16 kg load conditions.
[0036] Maleic anhydride-grafted hydrogenated styrene-ethylene / butene-styrene block copolymer (MAH-g-SEBS): The styrene structural unit mass fraction is 20%, and the maleic anhydride mass fraction of the raw materials used in Examples 1, 2 and 3 is 1.0%, 0.8% and 1.4%, respectively.
[0037] Polyisobutylene (PIB): Number average molecular weight is 55,000.
[0038] Hydrogenated alicyclic hydrocarbon resin: ring and ball softening point is 115℃, Gardner color number is 0.5, and refractive index at 25℃ is 1.51.
[0039] Naphthenic white oil: kinematic viscosity at 40°C is 110 mmHg 2 / s.
[0040] Single-terminated primary amine polyether: a polyoxypropylene ether with a primary amine at one end and a methoxy group at the other end, with a number average molecular weight of 1000 and a primary amine value of 0.94 meq / g per batch, which is equivalent to an amine value of 52.7 mg KOH / g based on KOH.
[0041] In this specification, the molar ratio of primary amine to maleic anhydride groups is calculated based on the primary amine value and maleic anhydride mass fraction of the raw material, and is not directly converted from the nominal number-average molecular weight. Using 100 parts by mass of MAH-g-SEBS as a baseline, assuming its maleic anhydride mass fraction is w (decimal), the primary amine value of the single-terminated primary amine polyether is A (meq / g), and the amount of single-terminated primary amine polyether used is m parts by mass, then: n(NH2)=m×A / 1000, n(MAH)=100×w / 98.06; When the target molar ratio is R, m = R × 100 × w × 1000 / (98.06 × A).
[0042] In this embodiment, A=0.94meq / g and R=1.04 were used for calculation.
[0043] To confirm the reaction modification of MAH-g-SEBS with the mono-terminated primary amine polyether, ATR-FTIR comparative tests can be performed on MAH-g-SEBS, the mono-terminated primary amine polyether, the unreacted physical mixture, and the reaction-modified product obtained in step A2. The test range is 4000-600 cm⁻¹. -1The determination is made by combining changes in the carbonyl absorption of maleic anhydride with the appearance of carbonyl absorption of amides and / or imides. The ATR-FTIR comparison test is used to qualitatively determine whether the reaction modification has occurred, and is not used to determine the quantitative conversion rate of maleic anhydride groups.
[0044] Example 1
[0045] 1. Preparation of single-ended polyether-modified flexible compatible components: Raw material ratio: 100 parts MAH-g-SEBS (maleic anhydride mass fraction 1.0%), 11.28 parts mono-terminated primary amine polyether, and 18 parts hydrogenated alicyclic hydrocarbon resin. Based on the primary amine value of 0.94 meq / g for mono-terminated primary amine polyether, n(NH2) = 11.28 × 0.94 / 1000 = 0.01060 mol; n(MAH) = 100 × 1.0% / 98.06 = 0.01020 mol; n(NH2) / n(MAH) = 1.04.
[0046] A1. MAH-g-SEBS and single-terminated primary amino polyether were dried at 80℃ and a gauge pressure of -0.090MPa for 3h to obtain dried MAH-g-SEBS and dried single-terminated primary amino polyether. A2. Add the dried MAH-g-SEBS to a closed mixing equipment and mix for 8 minutes under nitrogen protection, 160°C and 55r / min. Add the dried single-terminal primary amino polyether, heat to 180°C and mix for 50 minutes to obtain the reaction-modified product R1. A3. Add hydrogenated alicyclic hydrocarbon resin to the reaction-modified product R1, mix for 15 min at 175°C and 55 r / min, then devolatilize for 15 min at 175°C and a gauge pressure of -0.090 MPa, extrude and pelletize to obtain single-end polyether reaction-modified flexible compatibility component F1.
[0047] 2. Preparation of low-modulus hot-melt pressure-sensitive adhesive: Raw material ratio (parts by weight): HSIS 42 parts, PIB 16 parts, hydrogenated alicyclic hydrocarbon resin 35 parts, cycloalkyl white oil 10 parts, single-end polyether reaction-modified flexible compatibility component F1 8 parts, antioxidant 1010 0.4 parts, antioxidant 168 0.25 parts.
[0048] S1. HSIS, PIB, hydrogenated alicyclic hydrocarbon resin and single-ended polyether reaction-modified flexible compatibility component F1 were dried at 75℃ and a gauge pressure of -0.090MPa for 3h to obtain dried HSIS, dried PIB, dried hydrogenated alicyclic hydrocarbon resin and dried single-ended polyether reaction-modified flexible compatibility component F1. S2. Add the naphthenic white oil and the dried HSIS to a closed mixing equipment and mix for 28 minutes under nitrogen protection, 162°C and 60r / min to obtain the first mixed material. S3. Add the dried PIB and the dried single-ended polyether reaction-modified flexible compatibility component F1 to the first compound material, and mix for 22 minutes at 168°C and 60 r / min to obtain the second compound material. S4. Divide the dried hydrogenated alicyclic hydrocarbon resin into 3 batches of equal mass, add the first batch to the second compound material, and mix for 10 min at 168°C and 60 r / min. Add the second batch and mix for 10 min under the same conditions. Add the third batch and mix for 10 min under the same conditions to obtain the third compound material. S5. Add antioxidant 1010 and antioxidant 168 to the third compound material, and mix for 20 minutes at 168°C and 60 r / min to obtain the fourth compound material. S6. Degas the fourth compound material at 168°C and a gauge pressure of -0.090MPa for 15 minutes, filter it through a 180-mesh metal filter, and discharge it. The material temperature during filtration is 170°C to obtain low-modulus hot melt pressure-sensitive adhesive A1.
[0049] like Figure 1 As shown, the infrared absorption characteristics of MAH-g-SEBS, single-terminated primary amine polyether, unreacted physical mixture, and reaction-modified product R1 were compared. MAH-g-SEBS exhibited a distinct double peak in the aliphatic CH stretching vibration region and retained the characteristic absorption of styrene structural units and maleic anhydride carbonyl groups; the single-terminated primary amine polyether showed a broad NH absorption band and strong COC stretching vibration absorption of the polyether segments. The unreacted physical mixture basically showed a simple superposition of the peaks of the two raw materials, and the maleic anhydride carbonyl characteristics were still relatively clear; in the reaction-modified product R1, the maleic anhydride carbonyl double peak was significantly weakened and the peak shape changed, while a new broadened absorption band appeared in the carbonyl region, indicating that the primary amine and maleic anhydride groups underwent ring-opening amidation, possibly accompanied by partial dehydration imidization. Meanwhile, R1 still retains the strong COC absorption of the polyether segment and the characteristic peaks of the SEBS main chain, indicating that the flexible side chain of polyoxypropylene ether has been introduced into the MAH-g-SEBS structure, rather than being physically blended only in the form of free polyether. This indicates that the reaction-modified product R1 was formed in step A2 of Example 1. After adding hydrogenated alicyclic hydrocarbon resin to R1, a single-end polyether reaction-modified flexible compatible component F1 was obtained.
[0050] Example 2
[0051] 1. Preparation of single-ended polyether-modified flexible compatible components: Raw material ratio: 100 parts MAH-g-SEBS (maleic anhydride mass fraction 0.8%), 9.03 parts mono-terminated primary amine polyether, and 14 parts hydrogenated alicyclic hydrocarbon resin. Based on the primary amine value of 0.94 meq / g for mono-terminated primary amine polyether, n(NH2) = 9.03 × 0.94 / 1000 = 0.00849 mol; n(MAH) = 100 × 0.8% / 98.06 = 0.00816 mol; n(NH2) / n(MAH) = 1.04.
[0052] A1. MAH-g-SEBS and single-terminated primary amino polyether were dried at 78℃ and a gauge pressure of -0.088MPa for 3.5h to obtain dried MAH-g-SEBS and dried single-terminated primary amino polyether. A2. Add the dried MAH-g-SEBS to a closed mixing equipment and mix for 9 minutes under nitrogen protection, 158°C and 50 r / min. Add the dried single-terminal primary amino polyether, heat to 178°C and mix for 45 minutes to obtain the reaction-modified product. A3. Add hydrogenated alicyclic hydrocarbon resin to the reaction-modified product, mix for 14 min at 172°C and 50 r / min, then devolatilize for 14 min at 172°C and a gauge pressure of -0.088 MPa, extrude and pelletize to obtain single-end polyether reaction-modified flexible compatibility component F2.
[0053] 2. Preparation of low-modulus hot-melt pressure-sensitive adhesive: Raw material ratio (parts by weight): HSIS 38 parts, PIB 12 parts, hydrogenated alicyclic hydrocarbon resin 30 parts, cycloalkyl white oil 6 parts, single-end polyether reaction-modified flexible compatibility component F2 6 parts, antioxidant 1010 0.3 parts, antioxidant 168 0.15 parts.
[0054] S1. HSIS, PIB, hydrogenated alicyclic hydrocarbon resin and single-ended polyether reaction-modified flexible compatibility component F2 were dried at 70℃ and a gauge pressure of -0.088MPa for 3.5h to obtain dried HSIS, dried PIB, dried hydrogenated alicyclic hydrocarbon resin and dried single-ended polyether reaction-modified flexible compatibility component F2. S2. Add the naphthenic white oil and the dried HSIS to a closed mixing equipment and mix for 30 minutes under nitrogen protection, 158°C and 55r / min to obtain the first mixed material. S3. Add the dried PIB and the dried single-ended polyether reaction-modified flexible compatibility component F2 to the first compound material, and mix for 20 minutes at 165°C and 55 r / min to obtain the second compound material. S4. Divide the dried hydrogenated alicyclic hydrocarbon resin into two batches of equal mass, add the first batch to the second compound material, and mix for 12 minutes at 165°C and 55 r / min. Add the second batch and mix for 12 minutes under the same conditions to obtain the third compound material. S5. Add antioxidant 1010 and antioxidant 168 to the third compound material, and mix for 18 minutes at 165°C and 55 r / min to obtain the fourth compound material. S6. Degas the fourth compound material at 165°C and a gauge pressure of -0.088MPa for 14 minutes, filter it through a 160-mesh metal filter, and discharge it. The material temperature during filtration is 168°C, to obtain low-modulus hot melt pressure-sensitive adhesive A2.
[0055] Example 3
[0056] 1. Preparation of single-ended polyether-modified flexible compatible components: Raw material ratio: 100 parts MAH-g-SEBS (maleic anhydride mass fraction 1.4%), 15.80 parts mono-terminated primary amine polyether, and 22 parts hydrogenated alicyclic hydrocarbon resin. Based on the primary amine value of 0.94 meq / g for mono-terminated primary amine polyether, n(NH2) = 15.80 × 0.94 / 1000 = 0.01485 mol; n(MAH) = 100 × 1.4% / 98.06 = 0.01428 mol; n(NH2) / n(MAH) = 1.04.
[0057] A1. MAH-g-SEBS and single-terminated primary amino polyether were dried at 85℃ and a gauge pressure of -0.092MPa for 2.5h to obtain dried MAH-g-SEBS and dried single-terminated primary amino polyether. A2. Add the dried MAH-g-SEBS to a closed mixing equipment and mix for 7 minutes under nitrogen protection, 163°C and 65r / min. Add the dried single-terminal primary amino polyether, heat to 183°C and mix for 55 minutes to obtain the reaction-modified product. A3. Add hydrogenated alicyclic hydrocarbon resin to the reaction-modified product, mix for 18 min at 178°C and 65 r / min, then devolatilize for 18 min at 178°C and a gauge pressure of -0.092 MPa, extrude and pelletize to obtain single-end polyether reaction-modified flexible compatibility component F3.
[0058] 2. Preparation of low-modulus hot-melt pressure-sensitive adhesive: Raw material ratio (parts by weight): HSIS 48 parts, PIB 20 parts, hydrogenated alicyclic hydrocarbon resin 40 parts, cycloalkyl white oil 13 parts, single-end polyether reaction-modified flexible compatibility component F3 11 parts, antioxidant 1010 0.5 parts, antioxidant 168 0.35 parts.
[0059] S1. HSIS, PIB, hydrogenated alicyclic hydrocarbon resin and single-ended polyether reaction-modified flexible compatibility component F3 were dried at 82℃ and a gauge pressure of -0.092MPa for 2.5h to obtain dried HSIS, dried PIB, dried hydrogenated alicyclic hydrocarbon resin and dried single-ended polyether reaction-modified flexible compatibility component F3. S2. Add the naphthenic white oil and the dried HSIS to a closed mixing equipment and mix for 25 minutes under nitrogen protection, 168°C and 75r / min to obtain the first mixed material. S3. Add the dried PIB and the dried single-ended polyether reaction-modified flexible compatibility component F3 to the first compound material, and mix for 25 minutes at 172°C and 75 r / min to obtain the second compound material. S4. The dried hydrogenated alicyclic hydrocarbon resin is divided into 4 batches of equal mass. The first batch is added to the second compound material and mixed for 8 minutes at 172°C and 75 r / min. The second, third and fourth batches are added in sequence. After each batch is added, they are mixed for 8 minutes under the same conditions to obtain the third compound material. S5. Add antioxidant 1010 and antioxidant 168 to the third compound material, and mix for 22 minutes at 172°C and 75 r / min to obtain the fourth compound material. S6. Degas the fourth compound material at 172°C and a gauge pressure of -0.092MPa for 18 minutes, filter it through a 200-mesh metal filter, and discharge the material. The material temperature during filtration is 173°C, resulting in low-modulus hot melt pressure-sensitive adhesive A3.
[0060] Example 4
[0061] The preparation of an optical film bonding intermediate involves taking the low-modulus hot-melt pressure-sensitive adhesive A1 prepared in Example 1, heating it to 170°C to melt it, and coating it onto a 50 μm thick polyethylene terephthalate film, which serves as the first optical film, through a slit-type die. The thickness of the adhesive layer is controlled to be 25 μm. After cooling to room temperature, a 50 μm thick PET release film is laminated onto the adhesive layer surface with the release surface facing the adhesive layer. The film is then rolled back and forth three times with a 2 kg rubber roller at a speed of 300 mm / min to obtain the optical film bonding intermediate L1.
[0062] Following the above method, A2, a low-modulus hot-melt pressure-sensitive adhesive prepared in Example 2, was used to replace A1 to obtain optical film bonding intermediate L2; and A3, a low-modulus hot-melt pressure-sensitive adhesive prepared in Example 3, was used to replace A1 to obtain optical film bonding intermediate L3. When L2 was prepared using A2, the adhesive layer thickness was controlled to be 10 μm; when L3 was prepared using A3, the adhesive layer thickness was controlled to be 50 μm.
[0063] Comparative Example 1 A hot melt pressure-sensitive adhesive was prepared by referring to the preparation method in Example 1, except that the single-end polyether reaction-modified flexible compatibility component was replaced with an equal mass of HSIS (i.e., the total amount of HSIS was 50 parts). The other raw material types and amounts, preparation steps and process conditions were kept the same as in Example 1, and hot melt pressure-sensitive adhesive B1 was obtained.
[0064] Comparative Example 2 A hot melt pressure-sensitive adhesive was prepared by referring to the preparation method in Example 1, except that the single-end polyether reactive modified flexible compatibility component was replaced with an equal mass of unmodified maleic anhydride-grafted hydrogenated styrene-ethylene / butene-styrene block copolymer (HSEBS, styrene structural unit mass fraction 13%, commercially available). The other raw material types and amounts, preparation steps and process conditions were kept the same as in Example 1, and hot melt pressure-sensitive adhesive B2 was obtained.
[0065] Comparative Example 3 A hot melt pressure-sensitive adhesive was prepared by referring to the preparation method in Example 1, except that the single-end polyether reaction-modified flexible compatibility component was replaced with an equal mass of MAH-g-SEBS (maleic anhydride mass fraction 1.0%, unmodified by single-end polyether reaction), and the other raw material types and amounts, preparation steps and process conditions were kept the same as in Example 1, to obtain hot melt pressure-sensitive adhesive B3.
[0066] Comparative Example 4 A hot melt pressure-sensitive adhesive was prepared by referring to the preparation method in Example 1. The mass fraction of maleic anhydride in MAH-g-SEBS used in the preparation of the single-ended polyether reaction-modified flexible compatibility component was adjusted from 1.0% to 0.5%, and the amount of single-ended primary amino polyether was adjusted to 5.64 parts according to the primary amine value of 0.94 meq / g, so that the molar ratio of primary amino to maleic anhydride groups was maintained at 1.04. The types and amounts of other raw materials, preparation steps and process conditions were kept the same as in Example 1, and hot melt pressure-sensitive adhesive B4 was obtained.
[0067] Comparative Example 5 A hot melt pressure-sensitive adhesive was prepared by referring to the preparation method in Example 1. The mass fraction of maleic anhydride in MAH-g-SEBS used in the preparation of the single-ended polyether reaction-modified flexible compatible component was adjusted from 1.0% to 1.8%, and the amount of single-ended primary amino polyether was adjusted to 20.31 parts according to the primary amine value of 0.94 meq / g, so that the molar ratio of primary amino to maleic anhydride groups was maintained at 1.04. The types and amounts of other raw materials, preparation steps and process conditions were kept the same as in Example 1, and hot melt pressure-sensitive adhesive B5 was obtained.
[0068] Comparative Example 6 A hot melt pressure-sensitive adhesive was prepared according to the preparation method in Example 1. The number average molecular weight of the single-terminal primary amino polyether used in the preparation of the single-terminal polyether reaction-modified flexible compatible component was adjusted from 1000 to 500, and the amine value based on KOH was adjusted to 125 mg KOH / g (equivalent to 2.23 meq / g). The amount of the single-terminal primary amino polyether was adjusted to 4.76 parts, so that the molar ratio of primary amino to maleic anhydride groups was maintained at 1.04. The types and amounts of other raw materials, preparation steps and process conditions were kept the same as in Example 1, and hot melt pressure-sensitive adhesive B6 was obtained.
[0069] Comparative Example 7 A hot melt pressure-sensitive adhesive was prepared according to the preparation method in Example 1. The number-average molecular weight of the single-terminal primary amino polyether used in the preparation of the single-terminal polyether reaction-modified flexible compatible component was adjusted from 1000 to 1500, and the amine value based on KOH was adjusted to 38 mgKOH / g (equivalent to 0.677 meq / g). The amount of the single-terminal primary amino polyether was adjusted to 15.66 parts, so that the molar ratio of primary amino to maleic anhydride groups was maintained at 1.04. The other raw material types and amounts, preparation steps and process conditions were kept the same as in Example 1, and hot melt pressure-sensitive adhesive B7 was obtained.
[0070] Comparative Example 8 A hot melt pressure-sensitive adhesive was prepared by referring to the preparation method in Example 1. The amount of single-terminal primary amino polyether used in the preparation of the single-terminal polyether reaction-modified flexible compatible component was adjusted from 11.28 parts to 6.51 parts, and the molar ratio of primary amino to maleic anhydride groups was adjusted from 1.04 to 0.60. The types and amounts of other raw materials, preparation steps and process conditions were kept the same as in Example 1, and hot melt pressure-sensitive adhesive B8 was obtained.
[0071] Comparative Example 9 A hot melt pressure-sensitive adhesive was prepared by referring to the preparation method in Example 1, except that the amount of hydrogenated alicyclic hydrocarbon resin was adjusted to 48 parts, and the types and amounts of other raw materials, preparation steps and process conditions were kept the same as in Example 1, resulting in hot melt pressure-sensitive adhesive B9.
[0072] Comparative Example 10 A hot melt pressure-sensitive adhesive was prepared by referring to the preparation method in Example 1, except that the amount of cycloalkyl white oil was adjusted to 18 parts, and the types and amounts of other raw materials, preparation steps and process conditions were kept the same as in Example 1, to obtain hot melt pressure-sensitive adhesive B10.
[0073] Performance testing: Test film preparation: The hot-melt pressure-sensitive adhesives obtained in each example and comparative example were melted at 170±5℃ and coated onto a 50μm thick PET release film through a slit-type die. Another layer of PET release film was then applied, controlling the adhesive layer thickness to be 25±2μm. The resulting adhesive films were placed at 23±2℃ and 50±5% relative humidity for 24 hours before being used for various performance tests. The PET release film was used only as a carrier for film forming and transfer, and not as a backing material for peel strength and high-temperature tackiness tests.
[0074] 1.180° Peel Strength: Tested according to GB / T2792-2014. The test film was cut into 25mm wide and 200mm long samples. One side of the release film was removed, and the exposed adhesive surface was adhered to a 50μm thick ordinary PET film backing. The other side of the release film was then removed, and the other adhesive surface was adhered to a clean soda-lime glass plate. The plate was rolled back and forth three times with a 2kg rubber roller at a speed of 300mm / min. After being placed at 23±2℃ and 50±5% relative humidity for 20 minutes, a 180° peel test was performed at a speed of 300mm / min. Five parallel samples were tested in each group, and the arithmetic mean and standard deviation of the peel strength were reported.
[0075] 2. Shear storage modulus: Tested using the oscillating shear mode of a rotational rheometer. The gel sample was placed between parallel plates with a diameter of 25 mm and a test gap of 1.0 mm. Strain scans of 0.01%–10% were performed at 25 °C and 1 Hz to determine the linear viscoelastic region. Subsequently, at 0.1% strain and 1 Hz, the temperature was increased from -50 °C to 150 °C at a rate of 3 °C / min, and the shear storage modulus G' at 25 °C was recorded. Each sample was tested at least three times.
[0076] 3. Haze and transmittance: Tested according to GB / T2410-2008. Remove the release films from both sides of a 25±2μm thick test adhesive film, sandwich it between two identical clean soda-lime glass plates, and roll it back and forth three times with a 2kg rubber roller at a speed of 300mm / min to form a glass / adhesive / glass test specimen. Two identical soda-lime glass plates are directly stacked to form a reference specimen. Baseline correction is performed according to the instrument operating procedure. The haze and transmittance of the glass / adhesive / glass test specimen are measured and reported. Five parallel samples are tested in each group.
[0077] 4. Yellow Index: Tested according to GB / T39822-2021. The same glass / adhesive / glass test specimens as those used for haze and transmittance testing are used, and the yellow index is determined using a colorimeter; 5 parallel samples are tested in each group, and the arithmetic mean and standard deviation are reported.
[0078] 5. High-Temperature Adhesion Holding: Tested according to GB / T4851-2014. The test film was cut into 25mm wide samples. One side of the release film was removed, and the exposed adhesive surface was adhered to a 50μm thick ordinary PET film backing. The other side of the release film was then removed, and the other adhesive surface was adhered to a clean soda-lime glass plate, with an adhesion area of 25mm × 25mm. The sample was rolled back and forth three times with a 2kg rubber roller at a speed of 300mm / min, and placed at 23±2℃ for 20min. The sample was then placed vertically in an 80±2℃ environment, with a 1kg load suspended from the free end of the PET film backing. The time it took for the sample to completely detach or for the displacement to reach 25mm was recorded. Five parallel samples were tested in each group.
[0079] Table 1. Performance test results of each embodiment and comparative example
[0080] Table 1 shows that the examples, while maintaining high peel strength, significantly reduced shear storage modulus and achieved lower haze and yellow index, indicating that the introduction of flexible polyether side chains through reactive modification effectively enhanced system compatibility, suppressed macroscopic phase separation, and optimized the balance between physical crosslinking and chain segment mobility. In contrast, the comparative examples, due to the lack of reactive modification components, insufficient grafting rate, and imbalance in the proportion of plasticizer or tackifying resin, resulted in an imbalance between the cohesive strength and flexibility of the system, manifested as abnormally high or excessively low modulus, increased haze, intensified yellowing, and shortened high-temperature holding time. This reflects the negative impact of microscopic mechanisms such as free component migration, increased interfacial tension, and destruction of physical crosslinking points on macroscopic performance.
[0081] All performance tests were conducted by comparing samples from the same batch, with the same adhesive layer thickness and the same conditioning conditions. The original measured values, arithmetic mean and standard deviation of each parallel sample were recorded.
[0082] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A low-modulus hot-melt pressure-sensitive adhesive for optical thin film lamination, characterized in that, By weight, it includes the following raw materials: 38-48 parts of hydrogenated styrene-isoprene-styrene block copolymer, 12-20 parts of polyisobutylene, 30-40 parts of hydrogenated alicyclic hydrocarbon resin, 6-13 parts of cycloalkyl white oil, 6-11 parts of single-end polyether reaction-modified flexible compatibility component, 0.3-0.5 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and 0.15-0.35 parts of tris(2,4-di-tert-butylphenyl) phosphite; The single-ended polyether reactive modified flexible compatibility component is made from the following raw materials in parts by weight: maleic anhydride-grafted hydrogenated styrene-ethylene / butene-styrene block copolymer, single-ended primary amino polyether, and hydrogenated alicyclic hydrocarbon resin. The amount of hydrogenated alicyclic hydrocarbon resin in the low-modulus hot melt pressure-sensitive adhesive formulation does not include the hydrogenated alicyclic hydrocarbon resin contained in the single-end polyether reaction-modified flexible compatibility component. The single-ended polyether reaction-modified flexible compatible component is prepared according to the following steps: A1. 100 parts of maleic anhydride-grafted hydrogenated styrene-ethylene / butene-styrene block copolymer and single-terminal primary amino polyether were dried at 75-90℃ and a gauge pressure of -0.080 to -0.095 MPa for 2-4 hours to obtain dried maleic anhydride-grafted hydrogenated styrene-ethylene / butene-styrene block copolymer and dried single-terminal primary amino polyether. A2. The dried maleic anhydride-grafted hydrogenated styrene-ethylene / butene-styrene block copolymer is added to a closed mixing equipment and mixed for 5-10 minutes under nitrogen protection, 155-165℃ and 40-70r / min. The dried single-terminal primary amino polyether is added, the temperature is raised to 175-185℃ and mixed for 35-60 minutes to obtain the reaction-modified product. A3. Add 14-22 parts of hydrogenated alicyclic hydrocarbon resin to the reaction-modified product, mix for 10-20 min at 170-180℃ and 40-70 r / min, then devolatilize for 10-20 min at 170-180℃ and a gauge pressure of -0.080 to -0.095 MPa, extrude and pelletize to obtain the single-end polyether reaction-modified flexible compatibility component; The single-terminal primary amino polyether is a polyoxypropylene ether with a primary amino group at one end and a methoxy group at the other end, and has a primary amine value of 0.90-0.98 meq / g, which is equivalent to an amine value of 50.5-55.0 mgKOH / g based on KOH. When the maleic anhydride mass fraction of the maleic anhydride-grafted hydrogenated styrene-ethylene / butene-styrene block copolymer is 0.8%, 1.0%, and 1.4%, the amount of the single-terminal primary amino polyether relative to 100 parts of the maleic anhydride-grafted hydrogenated styrene-ethylene / butene-styrene block copolymer is 9.03 parts, 11.28 parts, and 15.80 parts, respectively, and the molar ratio of the primary amino group to the maleic anhydride group is 1.04 times.
2. The low-modulus hot-melt pressure-sensitive adhesive for optical thin film lamination according to claim 1, characterized in that, The melt flow rate of the hydrogenated styrene-isoprene-styrene block copolymer is 3-15 g / 10 min under conditions of 230 °C and 2.16 kg load.
3. The low-modulus hot-melt pressure-sensitive adhesive for optical thin film lamination according to claim 1, characterized in that, The number-average molecular weight of the polyisobutylene is 30,000-90,000.
4. The low-modulus hot-melt pressure-sensitive adhesive for optical thin film lamination according to claim 1, characterized in that, The hydrogenated alicyclic hydrocarbon resin has a ring and ball softening point of 95-125℃ and a Gardner color number not higher than 1.
5. A method for preparing a low-modulus hot-melt pressure-sensitive adhesive for optical thin film lamination as described in any one of claims 1-4, characterized in that, Includes the following steps: S1. The hydrogenated styrene-isoprene-styrene block copolymer, polyisobutylene, hydrogenated alicyclic hydrocarbon resin and single-ended polyether reaction-modified flexible compatibility component are dried at 65-85℃ and a gauge pressure of -0.080 to -0.095 MPa for 2-4 hours respectively. S2. Add the cycloalkyl white oil and hydrogenated styrene-isoprene-styrene block copolymer to a closed mixing equipment and mix for 20-35 minutes under nitrogen protection, 155-170℃ and 40-80r / min. S3. Add polyisobutylene and single-ended polyether reaction-modified flexible compatibility components, and mix for 15-30 minutes at 160-175℃ and 40-80r / min. S4. Add the hydrogenated alicyclic hydrocarbon resin in 2-4 batches of equal mass. After each batch is added, mix them at 160-175℃ and 40-80r / min for 8-15min. S5. Add pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl) phosphite, and mix for 15-25 minutes at 160-175℃ and 40-80 r / min. S6. Degas for 10-20 minutes at 160-175℃ and gauge pressure of -0.080 to -0.095 MPa, then filter through a 100-200 mesh metal filter to obtain the low modulus hot melt pressure-sensitive adhesive.
6. The preparation method according to claim 5, characterized in that, In steps S2 to S5, the material temperature inside the mixing equipment is maintained at 165-172℃; in step S6, a 150-180 mesh metal filter is used for filtration, and the material temperature is 165-175℃ during filtration.
7. An optical thin film bonding intermediate, characterized in that, The device includes a first optical film, a release material, and a hot-melt pressure-sensitive adhesive layer disposed between the first optical film and the release material. The first optical film is a polyethylene terephthalate film with a thickness of 50 μm. The release material is a PET release film with a thickness of 50 μm, and the release surface of the PET release film faces the hot-melt pressure-sensitive adhesive layer. The hot-melt pressure-sensitive adhesive layer is formed from the low-modulus hot-melt pressure-sensitive adhesive according to any one of claims 1-4, and the thickness of the hot-melt pressure-sensitive adhesive layer is 10-50 μm.
Citation Information
Patent Citations
Comb (block) copolymers
CN101595136A
Modified comb copolymers
CN101600740A
